PERAN OJK DALAM MENGAWASI PERKEMBANGAN BANK SYARIAH DI INDONESIA - Siti Aminah Nasution; Mhd. Alwi Syam Husyairi; Rafi Faizin (Prodi Perbankan Syariah UIN Sumatera Utara Medan, 2022)
The Monetary Administrations Authority as an establishment that regulates the Monetary Administrations Area, particularly in the financial area, necessities to complete its capabilities appropriately so the execution of exercises in the Monetary Administrations Area can run as it ought to and have the option to support financial development. The Monetary Administrations Authority has the position to administer Islamic Banks. Oversight of Islamic Banks is essential to do considering it is sidelined in empowering the speed of monetary development, particularly Miniature, Little and Medium Endeavors (MSMEs). Sharia banking supporting arrangements that contain absolution provisos are one of the lawful issues that happen in Islamic financial practices in Indonesia. The presence of an exemption statement in a funding contract frequently brings about misfortunes for the client since it incorporates the exchange of hazard to the client for the supporting made. This is in opposition to the fundamental standards of arrangements and Islamic regulation. The Monetary Administrations Authority (OJK) is a foundation ordered by Regulation No. 21 of 2008 concerning Sharia Banking to complete management of Sharia Banking in doing its functional exercises, including supporting agreements which are sharia banking items. This study expects to decide the job of management did by the Monetary Administrations Expert in creating Islamic Banks and to decide the degree to which the oversight cycle completed can tackle issues that exist in Islamic Banks. This study involves subjective information examination strategies to find nitty gritty clarifications for each checking movement completed. Three distinct information assortment techniques were utilized, specifically meetings, perception, and documentation. The aftereffects of this study are a clarification and elaboration of the targets of the Monetary Administrations Authority and the administrative cycle completed by the Monetary Administrations Expert in creating Islamic Banks.Otoritas Jasa Keuangan (OJK) sebagai lembaga yang mengatur di bidang Administrasi Moneter khususnya di bidang keuangan perlu melengkapi kemampuannya dengan baik agar pelaksanaan kegiatan di bidang Administrasi Keuangan dapat berjalan sebagaimana mestinya dan dapat mendukung pembangunan ekonomi. OJK memiliki posisi untuk mengelola Bank Syariah. Pengawasan terhadap Bank Umum Syariah sangat penting dilakukan mengingat dikesampingkan dalam memberdayakan percepatan pembangunan moneter, khususnya Usaha Mikro Kecil dan Mengengah (UMKM).Pengaturan penunjang perbankan syariah yang memuat ketentuan absolusi merupakan salah satu permasalahan hukum yang terjadi dalam praktik keuangan syariah di Indonesia. Kehadiran pernyataan pengecualian dalam kontrak pendanaan sering kali membawa kerugian bagi klien karena melibatkan pertukaran risiko kepada klien atas dukungan yang dibuat. Ini bertentangan dengan standar dasar pengaturan dan regulasi Islam. OJK adalah yayasan yang diperintahkan oleh Peraturan No. 21 Tahun 2008 tentang Perbankan Syariah untuk melengkapi pengelolaan Perbankan Syariah dalam menjalankan fungsinya, termasuk perjanjian pendukung yang merupakan item perbankan syariah.Studi ini diharapkan dapat menentukan pekerjaan manajemen yang dilakukan oleh OJK dalam menciptakan Bank Syariah dan untuk menentukan sejauh mana siklus pengawasan yang diselesaikan dapat mengatasi masalah yang ada di Bank Syariah. Studi ini melibatkan metode penelitian kualitatif untuk menemukan klarifikasi seluk beluk untuk setiap gerakan pemeriksaan yang diselesaikan. Teknik pemilahan informasi yang berbeda digunakan, khususnya observasi, wawancara dan dokumentasi. Hasil akhir dari penelitian ini adalah klarifikasi dan penjabaran target OJK dan siklus administrasi yang diselesaikan oleh OJK dalam mendirikan Bank Syariah.